Hemodynamic Analysis of VenaTech Convertible Vena Cava Filter Using Computational Fluid Dynamics - Wang, Jingying; Huang, Wen; Zhou, Yue; Han, Fangzhou; Ke, Dong; Lee, Chunhian (Frontiers in Bioengineering and Biotechnology, 2020)
The VenaTech convertible filter (VTCF) has been widely used as an inferior vena cava (IVC) filter to prevent fatal pulmonary embolism in patients. However, its hemodynamics that greatly affect the filter efficacy and IVC patency are still unclear. This paper uses computational fluid dynamics with the Carreau model to simulate the non-Newtonian blood flows around the VTCF respectively deployed in the normal, reverse and three converted states in an IVC model. The results show that the prothrombotic stagnation zones are observed downstream from the normal, reverse and small open VTCFs, with the streamwise length is nearly eight times the IVC diameter. The no-slip boundary conditions of the thin-wire VTCF arms lead to the ‘viscous block’ effect. The viscous block accelerates the blood flow by 5-15% inside the IVC and enhances the filter wall shear stress up to nearly 20 times that of the IVC only, which contributes to clot capture and thrombus lysis. The relative flow resistance is defined to evaluate the filter-induced resistance on the IVC blood flow that can be regarded as an index of IVC patency with the filter deployment. The flow resistance of the normal VTCF deployment increases dramatically by more than 60% compared with that of the IVC only and is a little higher (6%) than that of the reverse case. As the VTCF converts to a fully open configuration, the flow resistance gradually decreases to that of no filter. This work shows that even very thin VTCF arms can result in the viscous block effect and may cause significant hemodynamic impacts on clot capture, potential thrombosis and flow impedance inside the IVC. The present study also shows that CFD is a valuable and feasible in silico tool for analyzing the IVC filter hemodynamics to complement in vivo clinical and in vitro experimental studies.